The Effect of Organizational Commitment, Job Satisfaction, and Training on Protelindo Employee Performance With Organizational Citizenship Behavior (OCB) as A Mediating Variable - Andrian Garibaldi; Setyo Riyanto (Dinasti International Journal of Management Science, 2023)
By using Organizational Citizenship Behavior (OCB) as a mediating variable, this study aims to investigate the impact of organizational commitment, job satisfaction, and training on employee performance. Employees in the office of PT Profesional Telekomunikasi Indonesia were selected as subjects for this study. A total of 150 participants participated in this study using descriptive quantitative methodology. This study used SEM PLS data analysis, where the data processing used SmartPLS 3.0 application. The findings of this study indicate that training, job satisfaction, and organizational commitment have a beneficial and significant impact on job satisfaction. At the same time, OCB has an adverse and negligible effect on worker performance. Training has a positive but negligible impact on OCB, and the relationship between organizational commitment and job satisfaction has a considerable positive impact. Furthermore, OCB as a mediating variable has a negative and significant effect on mediating organizational commitment, job satisfaction, and training on employee performance.